Marianismo Beliefs, Intimate Partner Violence, and Psychological Distress Among Recently Immigrated, Young Adult Latinas - Silva, Nicole da (Journal of interpersonal violence, 2021)
Marianismo is a Latino cultural value that describes both positive and negative aspects of traditional Latina femininity. Marianismo emphasizes culturally valued qualities such as interpersonal harmony, inner strength, self-sacrifice, and morality. Endorsement of marianismo is hypothesized to correlate with individual economic, educational, and personal variables. Marianismo also is theorized to potentially influence attitudes about, experiences of, and responses to intimate partner violence (IPV) among Latina women. The present study examined whether endorsement of marianismo beliefs mitigated or exacerbated psychological distress after experiences of IPV in a sample of 205 recently immigrated Latina women, aged 18 to 23 years. Latina women experiencing higher levels of IPV and endorsing greater marianismo beliefs were hypothesized to indicate greater psychological distress. Unexpectedly, women who endorsed more Subordinate to Others/Self-Silencing to Maintain Harmony marianismo beliefs indicated more psychological distress (p = .05), greater symptoms of psychological distress (p = .01), and greater average distress (p = .03) when they also reported less IPV than peers. Implications for understanding Latinas’ responses to and reporting of IPV, as well as for culturally tailored counseling interventions for this underserved and understudied population, are discussed.